Composite dust suppressant suitable for surface mine transportation road and preparation method of composite dust suppressant
By combining xanthan gum with rhamnolipid and adding glycerin and magnesium chloride, a composite dust inhibitor suitable for open-pit mine transportation roads was prepared, which solved the inhibition of existing dust inhibitors on open-pit mine transportation roads. The dust duration is short, cost is high and toxic, which achieves an efficient, environmentally friendly and economical dust suppression effect.
Patent Information
- Application Number
- CN202411272382.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing dust inhibitors have problems such as short dust suppression duration, high cost, low efficiency, single function, toxicity and secondary pollution on open-pit mine transportation roads, especially the poor bonding performance of wet dust inhibitors and condensation type. Dust inhibitors have poor salt resistance and are toxic and difficult to degrade.
Using a composite dust inhibitor, the main components include binders, surfactants and hygroscopic agents. By combining xanthan gum with rhamnolipid and adding glycerin and magnesium chloride, a kind of easy to operate, low cost and inhibitory Dust inhibitor with good dust effect.
This composite dust inhibitor shows good evaporation resistance, wind corrosion resistance, compressibility and high dust suppression efficiency under atypical temperature, pH and salinity conditions. It is non-toxic and biodegradable, simple to operate and low-cost , suitable for open-pit mine transportation roads.
Smart Images

Figure CN119242268A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dust suppressants, in particular to a composite dust suppressant suitable for open-pit mine transportation roads. Background Art
[0002] As one of the methods of solid mining, open-pit mining is widely used due to its safety and efficiency, but environmental problems such as dust pollution also arise. Therefore, the dust control problem in open-pit mines has gradually become a research hotspot in the field of mine environmental protection. Currently, the commonly used dust suppression methods can be divided into physical dust suppression such as wet dust suppression and chemical dust suppression.
[0003] Wet dust suppression is widely used because of its simplicity and convenience, but its dust suppression duration is short, costly, and inefficient, making it difficult to achieve long-term dust suppression. Chemical dust suppression is achieved by capturing, adsorbing, and agglomerating dust particles, locking them in a mesh structure to achieve dust reduction, and is one of the effective methods for controlling dust problems. Although there are many types of dust suppressants, their single function, high price, toxicity, secondary pollution, and limited application in open-air environments are common problems. The main manifestations are that wet dust suppressants have poor bonding properties and a long curing time (usually 5-10 days); condensing dust suppressants have high costs and poor salt resistance; bonding dust suppressants made of residual oil, asphalt, etc. have poor hygroscopicity and have problems such as toxicity, difficulty in degradation, and pollution of water and soil. Although some effective dust suppressants have been developed, it is still necessary to develop environmentally friendly, efficient, and low-cost composite dust suppressants to solve the dust problem on open-pit mine transportation roads.
[0004] Xanthan gum is considered a powerful organic gum in the world. It is cheap, widely available, and has good thickening, emulsifying, suspending and stability properties. However, the slow penetration rate and low penetration efficiency of xanthan gum limit its application as a binder in open-pit mine transportation roads. Summary of the invention
[0005] The invention provides a composite dust suppressant suitable for open-pit mine transportation roads and a preparation method thereof. The main components of the composite dust suppressant include a binder, a surfactant, a hygroscopic agent and a water retaining agent. The surfactant is combined with xanthan gum, the binder and the surfactant are evenly mixed by a mixing method, and then the hygroscopic water retaining agent is added to prepare a composite dust suppressant suitable for open-pit mine transportation roads, which is easy to operate, has low economic cost and good dust suppression effect.
[0006] The composite dust suppressant of the present invention comprises a binder, a surfactant, a water retaining agent and a hygroscopic agent. In terms of the mass ratio with water, the amount of the binder and the surfactant is 0.1%-0.2% respectively, and the amount of the water retaining agent and the hygroscopic agent is 2%-4% respectively. The binder is xanthan gum, and the surfactant is rhamnolipid.
[0007] Preferably, the water retaining agent is glycerol.
[0008] Preferably, the hygroscopic agent is magnesium chloride.
[0009] The preparation method of the composite dust suppressant suitable for open-pit mine transportation roads comprises the following steps:
[0010] S1: Add 2%-4% xanthan gum to deionized water at 50-70°C according to the mass ratio with deionized water, and stir until a uniform xanthan gum solution is obtained;
[0011] S2: Add 2%-4% rhamnolipid dropwise to the stirred xanthan gum solution according to the mass ratio of rhamnolipid to deionized water, and stir until a uniformly mixed xanthan gum / rhamnolipid solution is obtained;
[0012] S3: Add 5%-7% of glycerol and magnesium chloride to deionized water according to the mass ratio of deionized water.
[0013] Continue stirring until a well-mixed solution is obtained;
[0014] S4: The solutions prepared by S2 and S3 are fully mixed in a volume ratio of 1-2:1-2, and stirred until a uniform mixed solution is obtained, which is a composite dust suppressant solution. The mixed solution is placed in a freeze dryer and dried, and then ground to obtain a composite dust suppressant powder.
[0015] Furthermore, the stirring described in S3 is performed at room temperature.
[0016] Furthermore, the stirring in S4 is performed at 50-70°C.
[0017] Furthermore, the drying time described in S4 is 12 hours.
[0018] The beneficial effects brought about by the technical solution provided by the present invention include at least:
[0019] The present invention combines xanthan gum and rhamnolipid, which not only utilizes the thickening, emulsification, suspension characteristics and stability of the xanthan gum organic gum, but also utilizes rhamnolipid, a biological surfactant, to reduce the surface tension of water and improve the penetration rate of the xanthan gum. The present invention can be used under atypical temperature, pH and salinity conditions, is non-toxic and biodegradable.
[0020] The present invention prepares a composite dust suppressant by compounding a surfactant with a main binder and then adding a hygroscopic and water-retaining agent. Due to the adhesiveness of the binder, the wettability of the surfactant, and the moisture retention and water absorption of the hygroscopic and water-retaining agent, the dust suppressant has good anti-evaporation, wind erosion resistance, compression resistance and high dust suppression efficiency. In addition, the preparation process of the composite dust suppressant meets the on-site application conditions, is simple and convenient to operate, and has low cost. It is a composite dust suppressant suitable for open-pit mine transportation roads. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 Moisture absorption experiment process diagram
[0023] Figure 2 The moisture content changes with time at different humidity levels
[0024] Figure 3 The graph of moisture content changing with time under different temperature conditions
[0025] Figure 4 Compression experiment process diagram
[0026] Figure 5 Compression curve of the specimen
[0027] Figure 6 A (left) and B (right) show the microscopic changes on the dust surface at 1000 times magnification.
[0028] Figure 7 Schematic diagram of dust fall simulation DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0030] Preparation process of composite dust suppressant:
[0031] (1) Add 2% to 4% xanthan gum to deionized water at 50 to 70° C. according to the mass ratio of xanthan gum to deionized water, and stir until a uniform xanthan gum solution is obtained;
[0032] (2) adding 2% to 4% rhamnolipid dropwise to the stirred xanthan gum solution according to the mass ratio of rhamnolipid to deionized water, and stirring until a uniformly mixed xanthan gum / rhamnolipid solution is obtained;
[0033] (3) adding 5% to 7% of glycerol and magnesium chloride to deionized water in a mass ratio to deionized water, and stirring continuously at room temperature until a uniformly mixed solution is obtained;
[0034] (4) The solutions prepared in (2) and (3) are fully mixed in a volume ratio of 1-2:1-2, and stirred at 50-70° C. until a uniform mixed solution is obtained, which is the composite dust suppressant solution. The mixed solution is placed in a freeze dryer and dried for 12 h, and then ground to obtain a composite dust suppressant powder.
[0035] Example 1: Response Surface Methodology
[0036] In this embodiment, the different ratios of the components of the composite dust suppressant are optimized by the response surface method to obtain the optimal ratio with the highest adhesion and anti-evaporation properties of the composite dust suppressant and a moderate pH value. The design is carried out according to the central composite design principle of Box-Benhnken, with xanthan gum, rhamnolipid, glycerol and magnesium chloride as independent variables, and pH value, viscosity and anti-evaporation properties as response values, and a four-factor three-level experimental design is carried out. The independent variable factors and their levels of this experimental design are shown in Table 1.
[0037] Table 1 Experimental independent variable factors and their levels
[0038]
[0039]
[0040] According to the four factors and three levels determined by BBD, the response surface test required 27 independent experiments in total using Design-Expert 13 software. The response surface test design results are shown in Table 2 Table 2 Response surface analysis factor combinations and experimental results
[0041]
[0042] According to the calculation results in Table 2, quadratic polynomials were used for fitting, and the regression equations of viscosity, pH value and anti-evaporation were obtained as shown in equations (1)-(3):
[0043]
[0044] The results of variance analysis of the regression model with different response values are shown in Table 3. It can be seen from the table that the F values corresponding to the three response values are 132.21, 14.75 and 28.09, respectively, and the values of Prob>F are all <0.0001, indicating that the model is significant. In addition, the Prob>F values in the lack of fit terms are 0.1635, 0.7920 and 0.3818, all of which are evaluated as insignificant, indicating that the model is less affected by errors. In summary, the quadratic equation model has significant regression, the lack of fit terms are not significant, and the fitting results are good. Therefore, the optimal ratio of the components of the composite chemical dust suppressant is obtained by using this model: 0.15% xanthan gum, 0.15% rhamnolipid, 3.2% glycerol and 2.8% magnesium chloride, with a predicted viscosity of 79.31 mPa·s, a pH value of 6.53, and an anti-evaporation property of 5.36%.
[0045] Table 3 Analysis of variance of regression models for each response value
[0046]
[0047]
[0048] The dust suppressant solution was prepared according to the optimal ratio, and its viscosity, pH and anti-evaporation properties were tested. Each group of experiments was carried out three times, and the obtained data were compared with the predicted values to analyze the rationality and effectiveness of the model optimization results. The results are shown in Table 4.
[0049] Table 4 Comparison of verification test results
[0050]
[0051] The viscosity, pH value and anti-evaporation of the dust suppressant measured by the experiment are close to the values predicted by the response surface model, indicating that this model is reasonable and effective, and can correctly predict the three response values of viscosity, pH value and anti-evaporation. Therefore, its optimization ratio result is correct. The viscosity of the dust suppressant under the optimal ratio is 81.98mPa·s, the pH value is 6.48, and the anti-evaporation is 5.20%. The dust suppressant under the optimal ratio obtained by the experiment is used in the subsequent embodiments, referred to as the optimal dust suppressant.
[0052] Example 2: Determination of moisture absorption
[0053] Prepare eight groups of 20.00g dry dust in a petri dish, spray the best dust suppressant and 5mL deionized water respectively, let it stand for 30 minutes, put it into a 100℃ forced air drying oven for 1h and take it out. At room temperature (i.e. 25℃), set the humidity of the GDJS-400A high and low temperature humidity test chamber to 30%, 50%, 70% and 90% respectively, put the dust sample containing the best dust suppressant solution and deionized water into the test chamber for experiment, take out the petri dish every hour, weigh and record the data, and carry out the experiment for 5 hours in total. The test process is as follows: Figure 1 shown.
[0054] The moisture content of dust samples changes with moisture absorption time at different humidity levels. Figure 2 As shown in the figure, after drying in a blast drying oven at 100°C for 1 hour, the moisture content of the four groups of dust samples sprayed with deionized water is lower than that of the dust samples sprayed with dust suppressants, indicating that the addition of dust suppressants can effectively inhibit the evaporation of water. Under different humidity, with the increase of moisture absorption time, the moisture content of dust samples gradually increases, but with the increase of humidity, the growth rate of moisture content continues to increase. Therefore, the addition of dust suppressants effectively increases the moisture absorption rate of dust samples, and the higher the humidity, the more obvious its effect.
[0055] Example 3: Anti-evaporation test
[0056] Weigh 10.00g of dry dust in 8 petri dishes with a diameter of 75mm, add 4 groups of 5.00g of deionized water and 4 groups of 5.00g of optimal dust suppressant solution, let it stand for 30 minutes, and put it into the blast drying oven after the solution is completely mixed with the dust sample. Set the temperature of the blast drying oven to 25℃, 35℃, 45℃ and 55℃ respectively, record a set of data every 30 minutes, and calculate the moisture content of the dust sample. The test time is 5h.
[0057] The results of the anti-evaporation test are as follows Figure 3 As shown in the figure, it can be seen that the dust sample sprayed with the optimal dust suppressant has a better anti-evaporation effect than the dust sample sprayed with deionized water. At the same temperature, the longer the drying time, the lower the moisture content of the dust sample. The moisture content of the dust sample sprayed with water decreases less than that of the dust sample sprayed with the dust suppressant solution. As the temperature increases, the rate of decrease in the moisture content of the dust sample gradually accelerates, and the final moisture content becomes smaller and smaller. However, at higher temperatures, the dust suppressant can still keep the dust at a certain humidity.
[0058] Example 4: Wind erosion resistance test
[0059] Weigh 20.00g of dry dust on a glass surface with an electronic balance, spray 1mL of the optimal dust suppressant solution and deionized water evenly on the dust surface, dry it at room temperature for 6 hours, and then put it in a 60℃ blast drying oven for 6 hours, and record the initial weight; finally, place the dust sample in an environment with different wind speeds for erosion, record the weight every hour, and calculate the loss rate at that moment, for a total of 5 hours. The calculation formula is shown in formula (4):
[0060]
[0061] Where: E——loss rate, %;
[0062] W 前 ——Mass of dust sample before blowing, g;
[0063] W 后 ——Mass of dust sample after erosion, g.
[0064] A hard shell is formed on the surface of dust sprayed with water and dust suppressant. Under the long-term action of wind, holes will appear on the hard shell formed on the surface of dust sprayed with water. The appearance of holes aggravates the damage of wind to the hard shell on the surface of dust, causing the holes to continue to grow. The dust inside will be lifted from the holes by the wind, forming a hollow shape. Eventually, the hard shell on the top collapses under the action of wind and loses its wind erosion resistance. However, the surface morphology of dust samples sprayed with dust suppressant remains basically unchanged, with basically no holes, and still has wind erosion resistance. Therefore, it can be concluded from the experimental process diagram that the addition of dust suppressant forms a hard shell with certain wind erosion resistance on the surface of dust, which can well protect the internal dust from being lifted again by wind.
[0065] The wind erosion resistance experimental data are shown in Table 5. The loss rate of dust samples sprayed with dust suppressants is generally lower than that of dust samples sprayed with deionized water. At a low wind speed of 3m / s, the wind force is too small to destroy the hard shell formed on the surface of the dust sample, and its loss rate mainly comes from the unconsolidated dust particles on the surface; at a wind speed of 6m / s, the wind force increases, causing a small number of small holes to appear in the hard shell on the surface of the dust. At this time, the loss rate mainly comes from the dust particles falling from the holes; at a wind speed of 10m / s, the loss rate of the two groups of dust samples increased significantly, and the loss rate mainly came from the loss of dust particles inside the holes. Therefore, the addition of dust suppressants greatly improves the wind erosion resistance of dust, especially at high wind speeds, the improvement effect is more obvious, which is consistent with the analysis results of the previous experimental process.
[0066] Table 5 Statistical table of dust sample loss rate at different wind speeds for 5 hours
[0067]
[0068]
[0069] Example 5: Corrosion Test
[0070] The corrosion of dust suppressant solution to metal was tested according to the "Metal Materials Laboratory Uniform Corrosion Full Immersion Test Method" (GB10124-88). Prepare three metal hanging pieces of 2024 aluminum alloy, Q235B carbon steel and 316 stainless steel with a size of 50mm (length) × 25mm (width) × 2mm (height), immerse them in alcohol for cleaning, take them out after cleaning, blow dry and weigh them; immerse them in 20mL of deionized water and the optimal dust suppressant solution respectively, take them out after soaking for 72h, wash them with alcohol, blow dry and weigh them, and calculate the corrosion rate according to the formula, the calculation formula is shown in formula (5):
[0071]
[0072] Where: X——corrosion rate, mm / a;
[0073] M 前 ——Mass of metal sheet before corrosion, g;
[0074] M 后 ——Mass of metal sheet after corrosion, g;
[0075] A——Surface area of metal sheet, cm 2 ;
[0076] T——test time, h;
[0077] D——metal sheet density, g / cm 3 .
[0078] From the perspective of surface morphology, the corrosion degree of carbon steel in deionized water is the highest, while the surfaces of aluminum alloy and stainless steel are basically unchanged. In the dust suppressant, the surfaces of aluminum alloy and carbon steel have corrosion marks to varying degrees, but the surface of stainless steel is basically unchanged.
[0079] Calculating the corrosion rates of different metal sheets shows Table 6. Deionized water has the least damage to stainless steel, with a corrosion rate of only 0.0012 mm / a, while it has the most severe damage to carbon steel, reaching 0.0397 mm / a. Dust suppressants are similar to deionized water, with the least effect on stainless steel, with a corrosion rate of only 0.0024 mm / a, and the most serious damage to carbon steel, which is 0.0496 mm / a. Therefore, it is recommended to ensure that the metal in contact with the dust suppressant solution is stainless steel in actual production to reduce corrosion. The corrosion rates of the two solutions on aluminum alloy are both 0.0036 mm / a, while the corrosion rates of the dust suppressant solution on stainless steel and carbon steel are greater than those of deionized water, indicating that the dust suppressant solution has a certain degree of corrosiveness, but the corrosion rates of the two solutions are similar, and the corrosion rate of the dust suppressant meets the requirements of "Technical Conditions for Dust Suppression in Railway Coal Transportation Part 1: Dust Suppressants", so the dust suppressant can be used in actual production.
[0080] Table 6 Corrosion rate of different metal sheets
[0081]
[0082] Example 6: Compression test
[0083] Weigh 50.00g of dry dust with an electronic balance and pour it into a mold with a diameter of 30mm. Pour 20mL of deionized water and the optimal dust suppressant solution and mix them evenly. Place it in a 100℃ forced air drying oven and dry it for 12 hours until constant weight is reached. After the sample cools to room temperature, demould and polish it to prepare a solidified dust column specimen. Use the Edberg HP series digital push-pull dynamometer to perform a compression test. Turn the screw until the specimen is crushed. The test process is as follows: Figure 4 shown.
[0084] The compression curves of the deionized water and dust suppressant specimens are shown in Figure 5 As shown in the figure, during the entire compression process, the deionized water specimen had one small rupture and one large rupture. The small rupture was mainly caused by the voids in the specimen. The appearance of the large rupture indicated that cracks began to appear on the surface of the specimen, and its compressive strength reached its peak. The dust suppressant specimen had two small ruptures and two large ruptures. The first large rupture indicated that the surface of the specimen began to rupture, and the appearance of the second large rupture indicated that a large rupture occurred again in the undamaged part of the surface of the specimen. At this time, the surface could no longer withstand greater force, and the compressive strength reached its peak. The hard shell formed on the surface of the deionized water specimen can only withstand one large rupture, while the surface of the dust suppressant specimen still has good compressive resistance after experiencing a large rupture, until the second large rupture occurs, and its compressive resistance decreases. At this time, the forces that cause the complete destruction of the two specimen surfaces are 0.27kN and 0.50kN respectively. In summary, the addition of dust suppressants effectively improves the compressive strength of dust, can well resist external forces, and plays a good consolidation role.
[0085] Example 7: Scanning electron microscopy experiment
[0086] Spray 5mL of deionized water and the best dust suppressant evenly onto the surface of 10g of dust, number them A and B respectively, and then put the two groups of dust samples into a freeze drying oven and dry them for 12 hours before taking out the dust samples. Stick the conductive glue tightly on the metal sample, ensuring that the edge does not exceed the sample stage, spread the dust sample evenly on the conductive glue, blow off the floating powder on the surface of the experimental sample, and put it into the Quorum SC7620 sputtering coater for gold spraying to improve the conductivity and secondary electron yield of the sample. Set the vacuum degree to 0.2mbar, the current size to 10mA, and the gold spraying time to 90s. Use the Czech TESCAN MIRA LMS scanning electron microscope for shooting. First, select the iconic point in the sample through the knob, adjust it to the center of the image, magnify it to a certain multiple, and adjust the knobs such as astigmatism, brightness, and contrast to obtain a clear image.
[0087] Observe and compare the microscopic surface morphology of the two groups of dust samples at 1000 times or greater magnification, such as Figure 6As shown, it can be found that the surface of dust particles in group A is relatively uniform overall. This is because after the dust samples in group A are sprayed with water, some small-sized dust particles are condensed on the dust particles with larger particle sizes after being moistened. These dust particles are very easy to break away from the dust body under the action of external force and disperse in the air, causing dust; while there are many dust particles of different sizes distributed on the surface of group B dust particles, indicating that under the action of dust suppressants, even dust particles with slightly larger particle sizes can be tightly adhered to large-sized particles. However, since the water is not completely dried, some large particles still remain in the dust samples in group A. After drying and grinding, some small particles adhering to the surface of large particles will fall off in the dust samples in group B, so there are still some fine particles in the microscopic surface diagram of the dust samples in group B. In general, the dust suppressant has a good dust-fixing and dust-suppressing effect.
[0088] Example 8: Dust fall simulation experiment
[0089] In order to test the dust reduction efficiency of the optimal dust suppressant, a simulated tunnel of 0.5×0.5×3m was built using aluminum profile brackets and transparent plastic film. An axial flow fan was placed in the front of the tunnel to simulate the dust lifting state; a funnel was installed at the top, and dust was added through the funnel to ensure that the dust could be evenly scattered in the tunnel; two spray devices were added at 2m in the tunnel, and water or the optimal dust suppressant was added through spraying to ensure that the spray range covered the entire square cross-section, creating a spray dust reduction atmosphere to avoid the formation of a single beam solution, resulting in uneven contact between the solution and the dust, affecting the dust reduction efficiency; an IFC-2 dust sampler was used at the end of the tunnel to measure the dust concentration in the tunnel, with the air volume set to 20L / min and the sampling time set to 5min. The experimental schematic diagram is shown below. Figure 7 shown.
[0090] This experiment is divided into two groups: total dust and respirable dust. Each group of experiments tests the dust concentration under three conditions: no water, water, and dust suppressant. The dust reduction efficiency of water and dust suppressant is calculated. Three parallel tests are conducted and the average value is taken. The calculation formulas for dust concentration and dust reduction efficiency are shown in equations (6) and (7):
[0091]
[0092] Where: C——dust concentration to be measured, g / m 3 ;
[0093] W1——filter membrane mass before sampling, g;
[0094] W2——mass of filter membrane after sampling, g;
[0095] q——sampling flow rate, L / min;
[0096] t——sampling time, min;
[0097]
[0098] Where: η——dust reduction efficiency, %;
[0099] C1——Dust concentration in the tunnel before spraying, g / m 3 ;
[0100] C2——Dust concentration in the tunnel after spraying, g / m 3 .
[0101] The dust reduction efficiency of water and dust suppressant on total dust and respirable dust is shown in Table 7 and Table 8. It can be concluded from the table that the dust reduction efficiency of water on total dust is 66.84% on average, and the dust reduction efficiency of dust suppressant on total dust is increased to 91.38%; the dust reduction efficiency of water on respirable dust is 54.64%, and the dust reduction efficiency of dust suppressant on respirable dust is increased to 81.22%. Therefore, compared with water, dust suppressant has better dust reduction efficiency, can effectively reduce the concentration of total dust and respirable dust, and is of great significance for actual production application.
[0102] Table 7 Dust reduction efficiency of two solutions on total dust
[0103]
[0104] Table 8 Dust reduction efficiency of two solutions on respirable dust
[0105]
[0106]
[0107] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A composite dust suppressant suitable for open-pit mine transportation roads, characterized in that: The invention comprises a binder, a surfactant, a water retaining agent and a hygroscopic agent. According to the mass ratio with water, the amount of the binder and the surfactant is 0.1%-0.2% respectively, and the amount of the water retaining agent and the hygroscopic agent is 2%-4% respectively. The binder is xanthan gum, and the surfactant is rhamnolipid.
2. The composite dust suppressant according to claim 1, characterized in that: The water retaining agent is glycerol.
3. The composite dust suppressant according to claim 1, characterized in that: The desiccant is magnesium chloride.
4. The method for preparing the composite dust suppressant according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Add 2%-4% xanthan gum to deionized water at 50-70°C according to the mass ratio with deionized water, and stir until a uniform xanthan gum solution is obtained; S2: Add 2%-4% rhamnolipid dropwise to the stirred xanthan gum solution according to the mass ratio of rhamnolipid to deionized water, and stir until a uniformly mixed xanthan gum / rhamnolipid solution is obtained; S3: adding 5%-7% of glycerol and magnesium chloride to deionized water according to the mass ratio of deionized water, and stirring continuously until a uniformly mixed solution is obtained; S4: The solutions prepared by S2 and S3 are fully mixed in a volume ratio of 1-2:1-2, and stirred until a uniform mixed solution is obtained, which is a composite dust suppressant solution. The mixed solution is placed in a freeze dryer and dried, and then ground to obtain a composite dust suppressant powder.
5. The preparation method according to claim 4, characterized in that: The stirring described in S3 is performed at room temperature.
6. The preparation method according to claim 4, characterized in that: The stirring in S4 is performed at 50-70°C.
7. The preparation method according to claim 4, characterized in that: The drying time described in S4 is 12 h.
Citation Information
Patent Citations
Dust inhibitor and preparation method thereof
CN101845291A
Dedusting agent and preparation method thereof
CN114958305A
Composite dust suppressant for suppressing flying dust of metal mine and preparation method of composite dust suppressant
CN118530695A
Scattering inhibitor using inorganic coagulants
KR101293257B1
Composition of hydrophilic gel type for inhibiting scattering dust and method for manufacturing the same
KR102017527B1
